Therapeutic advances in multiple sclerosis: Novel therapies (immune checkpoint inhibitors, CAR-T, Anti-CD40L) - Sarah E. Conway; Kristin Galetta (Neurotherapeutics)
As patients with multiple sclerosis (MS) age, the risk of cancer also increases. Immune checkpoint inhibitors (ICIs) are novel monoclonal antibodies that have revolutionized cancer treatment. However, their use is limited by immune related adverse events. In patients with MS and pre-existing autoimmune disease there is concern that use of ICIs could worsen disease outcome. In the first part of this review we discuss the current data on ICIs and MS which overall suggest that they are well tolerated from the standpoint of MS disease activity. We recommend that MS not be a strict contraindication to ICI use which should depend on an individualized risk benefit discussion. In the second part, we focus on novel therapies for MS including CAR-T cell and anti-CD40L treatments. These newer therapies have the potential to address an unmet need in MS as they can cross the blood-brain and have the potential to target compartmentalized central nervous inflammation that may underly the pathophysiology of progressive MS.